Virtual reality during pediatric vascular access: A pragmatic, prospective randomized, controlled trial. Issue 2 (19th December 2019) - Caruso, Thomas J.; George, Alexandria; Menendez, Maria; De Souza, Elizabeth; Khoury, Michael; Kist, Madison N.; Rodriguez, Samuel T.
Abstract: Background: Vascular access is a minor procedure that is associated with reported pain and fear in pediatric patients, often resulting in procedural incompliance. Virtual reality has been shown to be effective in adult populations for reducing pain and anxiety in various medical settings, although large studies are lacking in pediatrics. Aims: The primary aim was to determine whether pain would be reduced in pediatric patients using virtual reality undergoing vascular access. The four secondary aims measured patient fear, procedural compliance, satisfaction, and adverse events. Methods: A prospective, randomized, controlled trial was completed at a pediatric hospital, enrolling children 7‐18 years old undergoing vascular access in a variety of clinical settings, randomized to virtual reality or standard of care. Pain scores were measured using a numeric pain faces scale. The secondary outcomes of patient fear, procedural compliance, satisfaction, and adverse events were measured with the Child Fear Scale, modified Induction Compliance Checklist, and satisfaction surveys, respectively. Chi‐squared, t tests, and regression models were used to analyze the results. Results: The analysis included 106 patients in the virtual reality group and 114 in the control. There were no significant differences in postprocedure pain (VR group estimated 0.11 points lower, 95% confidence interval: 0.50 points lower to 0.28 points greater, P = .59), postprocedure fear (VR group estimated 0.05 points lower, 95% confidence interval: 0.23 points lower to 0.13 points greater), or compliance (adjusted odds ratio 2.31, 95% confidence interval: 0.96‐5.56). Children in the virtual reality group were satisfied with the intervention. There were no adverse events. Conclusion: This study demonstrates no reduction in pain while using Virtual reality (VR) across a heterogeneous pediatric inpatient population undergoing vascular access.